Cognitive Decline after Delirium in Patients Undergoing Cardiac Surgery. (September 2018) - Brown, Charles H.; Probert, Julia; Healy, Ryan; Parish, Michelle; Nomura, Yohei; Yamaguchi, Atsushi; Tian, Jing; Zehr, Kenton; Mandal, Kaushik; Kamath, Vidyulata; Neufeld, Karin J.; Hogue, Charles W.
Abstract : What We Already Know about This Topic: Cardiac surgery is associated with cognitive decline and postoperative delirium The relationship between postoperative delirium and cognitive decline after cardiac surgery is unclear What This Article Tells Us That Is New: The development of postoperative delirium is associated with a greater degree of cognitive decline 1 month after cardiac surgery The development of postoperative delirium is not a predictor of cognitive decline 1 yr after cardiac surgery Background: Delirium is common after cardiac surgery and has been associated with morbidity, mortality, and cognitive decline. However, there are conflicting reports on the magnitude, trajectory, and domains of cognitive change that might be affected. The authors hypothesized that patients with delirium would experience greater cognitive decline at 1 month and 1 yr after cardiac surgery compared to those without delirium. Methods: Patients who underwent coronary artery bypass and/or valve surgery with cardiopulmonary bypass were eligible for this cohort study. Delirium was assessed with the Confusion Assessment Method. A neuropsychologic battery was administered before surgery, at 1 month, and at 1 yr later. Linear regression was used to examine the association between delirium and change in composite cognitive Z score from baseline to 1 month (primary outcome). Secondary outcomes were domain-specific changes at 1 month and composite and domain-specific changes at 1 yr. Results: The incidence of delirium in 142 patients was 53.5%. Patients with delirium had greater decline in composite cognitive Z score at 1 month (greater decline by −0.29; 95% CI, −0.54 to −0.05; P = 0.020) and in the domains of visuoconstruction and processing speed. From baseline to 1 yr, there was no difference between delirious and nondelirious patients with respect to change in composite cognitive Z score, although greater decline in processing speed persisted among the delirious patients. Conclusions: Patients who developed delirium had greater decline in a composite measure of cognition and in visuoconstruction and processing speed domains at 1 month. The differences in cognitive change by delirium were not significant at 1 yr, with the exception of processing speed. Abstract : The development of postoperative delirium is associated with a greater degree of cognitive decline 1 month after cardiac surgery. The development of postoperative delirium is not a predictor of cognitive decline 1 yr after cardiac surgery.